Theoretical Research on Foreign Language Learning Anxiety Among English Major Students - Guo Nyuhuan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Foreign language learning anxiety is a prevalent emotional phenomenon among English major students that significantly impacts their learning effectiveness and motivation. This study comprehensively examines the definition, classification, causes, and complex effects of foreign language learning anxiety from a theoretical perspective. Through analyzing the interplay of personal factors (such as self-esteem, learning styles, learning motivation) and environmental factors (such as teaching methods, classroom atmosphere, test pressure, cultural differences), it reveals the multidimensional nature of foreign language learning anxiety. The research indicates that this anxiety not only reduces learners' motivation and efficiency but also interferes with their cognitive processes, affects the development of speaking and listening skills, and even negatively impacts their physical and mental health. To address this issue, based on the Affective Filter Hypothesis, Humanistic Psychology, Constructivist Learning Theory, and Social Interaction Theory, this study proposes educational intervention strategies, including optimizing curriculum design, improving teaching evaluation systems, establishing psychological counseling mechanisms, and strengthening the emotional support function of teachers. These strategies aim to create a positive, interactive learning environment to help students overcome anxiety and enhance learning outcomes.